Cold atom gravimeter - Marinčič, Matevž (Matrika, 2016)
In this article some basic and widely used cooling and trapping techniques for obtaining cold atom gases are presented. Amongst those are optical molasses, evaporative cooling, and magneto-optical trap. The most important physical properties of cold atoms are stressed in an introduction to cold atom interferometry. The principles of cold atom gravity meter are explained to some extent. It has many benefits and better accuracy compared to classical gravimeters. Potential uses in geodesy, navigation, earth's gravity field mapping, as gravity wave detectors, and for testing fundamental gravitational laws and theories are also briefly discussed.
Keywords: atomic physics; atomska fizika; cold atoms; cooling techniques; gravimeter; hlajenje atomov